An Italian Translation and Validation of the near Activity Visual Questionnaire (NAVQ). Issue 6 (8th November 2017) - Zeri, Fabrizio; Beltramo, Isabella; Boccardo, Laura; Palumbo, Paolo; Petitti, Vincenzo; Wolffsohn, James S.; Naroo, Shehzad A.
Purpose: To validate the Near Activity Vision Questionnaire (NAVQ) in Italian to allow the assessment of presbyopia corrections in Italian-speaking patients. Methods: An Italian version of the NAVQ was arranged through several steps: an initial forward translation (from English to Italian), a backward translation (from Italian to English), and finally a consensual version to check against the original NAVQ. This prospective study enrolled native Italian-speaking presbyopic patients with corrected distance visual acuity of 0.20 logMAR or better in each eye and free of ocular anomalies. Six different groups of patients were asked to complete the questionnaire: emerging presbyopic patients, reading spectacle users, multifocal spectacle users, multifocal contact lens (CL) wearers, monovision CL wearers, and monofocal intraocular lens patients. Subjects were asked to answer the questionnaire again 2 weeks after the first completion. Results: A total of 207 subjects completed the questionnaire. Data analysis showed good internal consistency (Cronbach α = 0.93) and factorial validity with only one factor explaining 62.0% of the variance. Test-retest reliability was extremely good (ICC = 0.92) as well as discriminatory power of the questionnaire's ability to discriminate between subjects with different forms of presbyopic correction. Conclusions: The Italian version of the NAVQ matches the properties of the original English version. It is a valid instrument to evaluate near activity visual quality of presbyopic Italian speakers.